1986
DOI: 10.1007/bf00338077
|View full text |Cite
|
Sign up to set email alerts
|

DNase I sensitivity of the chromatin of the yeast SUC2 gene for invertase

Abstract: The DNase I sensitivity of chromatin of the yeast SUC2 gene, which encodes two forms of invertase, has been studied both in the genome and in a multicopy plasmid carrying the gene and its flaking sequences. Whereas little if any difference in the DNase I sensitivity of the flanking regions was found between the repressed and the derepressed states, derepression of the gene was accompanied by a large increase in the sensitivity of the transcribed region. A well-defined DNase I hypersensitive site was found cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Ladders of fuzzy bands both upstream and downstream of the hypersensitive site were visible, especially in the repressed state. This kind of DNase I bands has been previously found in yeast and interpreted as the result of a somewhat preferential attack to linker DNA (Perez-Ortin et al, 1986a, 1987Szent-Giorgyi et al, 1987). Identical results were obtained with the genomic copy of FBPI when the experiments were carried out with untransformed CJM88 cells (not shown).…”
Section: A) Promoter (Probe Eh)supporting
confidence: 66%
See 1 more Smart Citation
“…Ladders of fuzzy bands both upstream and downstream of the hypersensitive site were visible, especially in the repressed state. This kind of DNase I bands has been previously found in yeast and interpreted as the result of a somewhat preferential attack to linker DNA (Perez-Ortin et al, 1986a, 1987Szent-Giorgyi et al, 1987). Identical results were obtained with the genomic copy of FBPI when the experiments were carried out with untransformed CJM88 cells (not shown).…”
Section: A) Promoter (Probe Eh)supporting
confidence: 66%
“…At any rate, it is remarkable that hypersensitive sites close to the 3' end have been found in many yeast genes, e.g. SUC2 (Perez-Ortin et al, 1986a), HSP82 (Szent-Giorgyi et al, 1987), TRPl (Thoma et al, 1984), CZN2 (Lee and Garrard, 1991), URA3 (Thoma, 1986). In all these cases the hypersensitive sites are flanked by positioned nucleosomes and in some instances it has been shown that positioning results from a boundary effect due to the structure of the hypersensitive site (Matallana et al, in preparation;Thoma, 1986).…”
Section: Chromatin Structure Of the 3'jlankmentioning
confidence: 99%
“…Another interesting feature of the promoter structure is the fact that the hypersensitive site becomes MNase resistant upon activation (compare for example in Figure 3, CHA4 −Ser and +Ser), although it maintains its accessibility to DNase I (compare for example Figure 1, +Ser with Figure 3, CHA4 +Ser). This peculiar change has been observed in other genes, namely in the UAS of the GAL1‐10 genes (Lohr and Hopper, 1985) and in the regulatory region of the SUC2 gene (Perez‐Ortin et al ., 1986, 1987) under derepressed conditions. In the CHA1 promoter, this change is specifically dependent on the transcriptional state of the gene, that is, even under derepressed conditions this MNase‐specific protection is not seen unless the gene is actively being transcribed.…”
Section: Discussionmentioning
confidence: 69%
“…This basal acetylation is high around the upstream activating sequence (Fig. 2), where a DNase I hypersensitive site exists (1). A relatively high, transcription-independent, basal level of histone acetylation is common in yeast (48), but the mechanisms for maintaining this nontargeted level of acetylation are not clear.…”
Section: Discussionmentioning
confidence: 99%